Manifestations of Polycystic Ovary Syndrome are Similar Regardless of the Degree of Menstrual Cycle Variation - Zamila, Begum Moriom; Banu, Hurjahan; Morshed, Md Shahed; Shah, Sukanti; Begum, Afroza; Sultana, Tania; Akhtar, Nazma; Fariduddin, Md; Saleh, Ahmed Abu; Hasanat, MA (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Menstrual irregularities may predict over adverse consequences in polycystic ovary syndrome (PCOS). Objective: To observe the relation of variants of menstrual cycles with clinical and biochemical features of PCOS. Methods: This cross-sectional study encompassed 200 PCOS women diagnosed by Rotterdam criteria and 120 age-matched healthy controls. Subgroups were classified according to menstrual cycle length as: polymenorrheic (<21 days), eumenorrheic (21-35 days), oligomenorrheic (36 days-3 months) and amenorrheic (>3 months). Glucose was measured by glucose oxidase, lipid by glycerol phosphate dehydrogenenase-peroxidase and all hormones by chemiluminescent immuno-assay method. Results: Around 86% of PCOS patients had menstrual irregularity, among which 75% had oligomenorrhea followed by amenorrhea (9%) and polymenorrhea (2%). All the subgroups of PCOS patients (polymenorrhea excluded from further analyses) had significantly poor metabolic manifestations than the control namely insulin resistance (IR), impaired glycaemic status, general and central obesity, metabolic syndrome and dyslipidaemia. Acanthosis nigricans (AN), hyperandrogenemia (HA) and IR had significant predictive association with PCOS patients with both irregular [OR (95% CI)- AN: 21.994 (6.427, 75.267), p<0.001; HA: 27.735 (8.672, 88.704), p<0.001; IR: 7.268 (2.647, 19.954), p<0.001] and regular cycle [AN: 16.449 (3.830, 70.643), p<0.001; HA: 24.635 (6.349, 95.590), p<0.001; IR: 6.071 (1.658, 22.234), p=0.006] in reference to control group. None of the variables had significant predictive associations with irregular cycle in reference to regular cycle in patients with PCOS. Conclusion: Oligomenorrhea was the most common variant of menstrual irregularity in PCOS patients. All menstrual variants including eumenorrhea had similar manifestations in PCOS women, but poorer than controls. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 96-103